Formation of sweet potato starch nanoparticles by ultrasonic—assisted nanoprecipitation: Effect of cold plasma treatment - Wang, Jian; Yu, Yu-Die; Zhang, Zhi-Guo; Wu, Wei-Cheng; Sun, Pei-Long; Cai, Ming; Yang, Kai (Frontiers in Bioengineering and Biotechnology, 2022)
Starch nanoparticles (SNPs) were produced from sweet potato starches by ultrasonic treatment combined with rapid nanoprecipitation. The starch concentration, ultrasonic time, and the ratio of starch solution to ethanol were optimized through dynamic light scattering (DLS) technique to obtain SNPs with a Z-average size of 64.51 ± 0.15 nm, poly dispersity index (PDI) of 0.23 ± 0.01. However, after freeze drying, the SNPs showed varying degrees of aggregation depending on the particle size of SNPs before freeze-drying. The smaller the particle size, the more serious the aggregation. Therefore, we tried to treat SNPs with dielectric barrier discharge cold plasma before freeze drying. Properties including morphological features, crystalline structure and apparent viscosity of various starches were measured by field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), and rheometer, respectively. The results showed that, after cold plasma (CP) treatment, the aggregation of SNPs during freeze drying was significantly inhibited. Compared to the native sweet potato starch, SNPs showed a higher relative crystallinity and a lower apparent viscosity. After CP treatment, the relative crystallinity of CP SNPs was further higher, and the apparent viscosity was lower. This work provides new ideas for the preparation of SNPs and could promote the development of sweet potato SNPs in the field of active ingredient delivery.